Marketing Zambia as a tourism destination : e-challenges, e-strategies and opportunities for the Zambia National Tourist Board - Sheba, M. K. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.